Using ARCH and GARCH mathematical models to predict the general budget deficit for the period from (2008) to (2023) - Saad Obaid Jameel AL-Masoodi (Wasit Journal for Pure Sciences)
: In this research, (ARCH) and (GARCH) were used, which are mathematical models for time series, as the study of time series is considered one of the topics of great importance in analyzing the behavior of various phenomena and interpreting them by analyzing their change according to time, adopting different time periods. Among the most prominent time series are series Finance, which is volatile, that is, characterized by the characteristic of instability (volatility), which makes the use of (ARMA) models inaccurate in its predictive results, which work on the assumption that the variance of the random error, which is distributed normally, and which is constant over time. As for time series, this condition is This is not true and it shows variation and fluctuations at different periods of the series.